Seeing the air quality of carbon monoxide in Makassar city: the CSR program of PT Pertamina IT - Krisno Bimantoro; Andi Ade Ula Saswini; Mustofa Mustofa (Al-Sihah : The Public Health Science Journal, 2020)
The high number of residents in urban areas accompanied by an increase in motor vehicle users can be a trigger for increasing concentrations of Carbon monoxide emissions. The purpose of this monitoring activity is as follows, namely to obtain air quality data / information on CO (carbon monoxide) parameters as a basis for comparing the air quality of CO parameters before and after the CSR (corporate social responsibility)  Program Asri Wall which is then analyzed based on the Air Pollution Standard Pollution Index (ISPU). Air quality monitoring is carried out in three locations of Intervention CSR Program which has the potential to cause air pollution, especially carbon monoxide (CO) gas impact on public health. The results of air quality monitoring showed the average value of CO concentrations during / before the implementation of the CSR Wall Asri program was higher, compared to after the implementation of the CSR program. The Value Analysis of the Air Pollution Standard Index (ISPU) during / before the implementation of the CSR program is more dangerous to health and is categorized as Very Unhealthy, while the ISPU value after the implementation of this CSR Program has decreased in value and is in the Unhealthy category. Therefore, it can be concluded that the air quality at the CSR Program Intervention Location experienced an improvement in air quality after the implementation of the Asri CSR Program.